Estimation of Income Taxation Function in Sudan for the Period (1992-2020) - Nour, Ali Elhassan Mohammed; Seed, Mohsin Mahir; Abdelmotalib, MohiyEldeen Mohmed (Journal of Economic, Administrative and Legal Sciences, 2022)
This study tried to exam income tax in the Sudan; in this regard the study aims to examine the relationship between income tax and GDP, as well as identifying the income tax characteristics in the Sudan. The study depends on the assumption that income tax related positively to GDP, and it has a progressive type in Sudan. The study used the historical and analytical methodology, using for that (OLS) method for a series data during the period 1992-2020. The results of the study revealed that the relationship between income tax and GDP is positive and it was progressive in Sudan. The study recommended the necessity of tax evasion treatment, and activates income tax, so to serve the orientations of fiscal policy, to contribute in equality, and income redistribution in Sudan.